KAPASITAS PETANI DALAM USAHATANI HIDROPONIK DI KOTA KENDARI - Posad, Andriawan Saputra; Abdullah, Sukmawati; Jayadisastra, Yoenita; Buana, Tjandra (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The objective of this study is to evaluate the hydroponic farming capacity of farmers in Kendari City. The study population consists of 25 hydroponic farmers identified in the Kendari City Agriculture Office database. The sample was determined using the census method by taking the entire population. Research data were collected through surveys, interviews, and documentation using questionnaires as the medium. Descriptive quantitative analysis with the class interval formula was used for data analysis. The results indicate that the capacity of farmers in hydroponic farming in Kendari City is classified as high based on their level of knowledge, attitudes, and skills. The majority of hydroponic farmers have a productive age and possess qualified education to support farming activities, especially with hydroponic systems. Their knowledge, attitudes, and skills are very good.